2019
DOI: 10.1002/yea.3427
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in yeast: Segregation error or adaptation mechanism?

Abstract: Aneuploidy is the loss or gain of chromosomes within a genome. It is often detrimental and has been associated with cell death and genetic disorders. However, aneuploidy can also be beneficial and provide a quick solution through changes in gene dosage when cells face environmental stress. Here, we review the prevalence of aneuploidy in Saccharomyces, Candida, and Cryptococcus yeasts (and their hybrid offspring) and analyse associations with chromosome size and specific stressors. We discuss how aneuploidy, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
117
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 125 publications
(263 reference statements)
16
117
1
Order By: Relevance
“…S11, S12). Chromosome loss, consistent with previous studies (for review 44 ), more frequently affects the smallest chromosomes (I and III) in diploid hybrids, probably because it affects a smaller number of genes. However, larger chromosome losses (II, V and VIII) are observed in tetraploids, suggesting a potentially less deleterious effect of their loss due to the multiple copies present in the cell.…”
Section: Main Textsupporting
confidence: 91%
“…S11, S12). Chromosome loss, consistent with previous studies (for review 44 ), more frequently affects the smallest chromosomes (I and III) in diploid hybrids, probably because it affects a smaller number of genes. However, larger chromosome losses (II, V and VIII) are observed in tetraploids, suggesting a potentially less deleterious effect of their loss due to the multiple copies present in the cell.…”
Section: Main Textsupporting
confidence: 91%
“…Aneuploidy, large-scale chromosomal rearrangements, and LOH are ubiquitous genomic alterations in solid tumor cells, as well as in yeast population (Zhu et al 2016, Heil et al 2017, Sansregret and Swanton 2017, Cho and Jinks-Robertson 2019, Gilchrist and Stelkens 2019. Many studies suggest that these genetic events would promote the adaptive evolution of yeast cells in response to environmental stimulus or genetic perturbations (Tan et al 2013, Gerstein et al 2015, Heil et al 2017, Hose et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Then, when the environment changes back or when other adaptive mutations optimising the specific trait under selection relieve the stress, the ancestral configuration could be restored, readying the population for the next unpredictable change. Indeed, authors have suggested that this kind of reversible chromosomal change in yeast might itself be a general adaptive strategy to an unpredictably changing environment (Gilchrist and Stelkens 2019, Dunham et al 2002, Infante et al 2003, Cox and Bevan 1962. If this inference is correct, we would predict that the rate of production of chromosomal variants would evolve to reflect the probability of environmental fluctuation, as a form of biological bet-hedging (de Jong et al 2011).…”
Section: Introductionmentioning
confidence: 97%